The Effect of the GeoGebra Application on Students’ Mathematical Reasoning Abilities - Lubis, Ari Aulia Abdi; Novitasari, Wiwik; Fitriani, Fitriani; Amanda, Saksi; Rezvani, Mohammad Qais (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
Background: This program addresses the low mathematical reasoning ability and minimal technology use at MA Negeri 4 Mandailing Natal by implementing the GeoGebra application. GeoGebra is a dynamic software integrating geometry, algebra, and calculus, helping students visualize abstract mathematical concepts in a concrete and engaging way.Aims: This program aims to examine the significant influence of using the GeoGebra application on students' mathematical reasoning.Methods: This program employed a pre-experimental one-group pretest-posttest design. The sample was 30 students from class X MIPA C at MA Negeri 4 Mandailing Natal, selected via simple random sampling. Instruments included mathematical reasoning tests and questionnaires. Data were analyzed quantitatively using simple linear regression analysis.Results: Results showed a positive and significant influence of GeoGebra on students' mathematical reasoning abilities. A simple linear regression analysis yielded a significance value (p < 0.05) and the equation Y = 67.367 + 7.300X. An improvement was also observed descriptively: the number of students who successfully completed the reasoning test increased from 10 (out of 30) in the pre-test to 20 in the post-test.Conclusion: This program concludes that increased GeoGebra utilization is associated with higher students’ reasoning abilities. The findings empirically confirm GeoGebra as an effective pedagogical tool. Therefore, its use is recommended as an interactive mathematics learning medium to help students visualize abstract concepts and improve reasoning outcomes.